PENGARUH ROLE CONFLICT DAN KOMPETENSI TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI (Studi Kasus pada Kantor Inspektorat Kota Pontianak dan Inspektorat Provinsi Kalimantan Barat) - Lieanti, Tasya Devi (ABDI EQUATOR, 2024)
This research aims to determine the effect of role and competency conflict on auditor performance with emotional intelligence as a moderating variable at the Pontianak City and West Kalimantan Province Auditor's Office. This research uses a questionnaire with a Likert scale to obtain the data. The population and sample in this study were auditors who worked at the Pontianak City Auditor's Office and West Kalimantan Province with a minimum tenure of one year, with data obtained from 42 respondents. The results of this research show that role conflict has a positive and insignificant effect on auditor performance, competence has a positive and significant effect on auditor performance, emotional intelligence cannot strengthen the effect of role conflict and competence on auditor performance.